Optimal Pricing Policies For Deteriorating items With Preservation Technology And Price Sensitive Demand - Shah, Nita H.; Shah, Arpan D. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
This paper considers the problem of determining the price, cycle time and preservation technology cost strategies for deteriorating items. It is assumed that preservation technology investment and demand rate do follow the function of selling price. The objective is to maximize the total profit per unit time with determining the optimal selling price, length of replenishment cycle and preservation technology investment. We will be proving that the optimal cycle length and selling price are unique with respect to given preservation cost. Also, total profit per unit time will be a concave function as it will reach its optimum value for optimum value of selling price, cycle length and preservation technology cost. Numerical examples are also presented to demonstrate the solution process.